2014
DOI: 10.1016/j.watres.2014.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of biofilm and corrosion of cast iron pipes in drinking water distribution system with UV/Cl2 disinfection

Abstract: Corrosion DisinfectionWater quality Drinking water distribution system a b s t r a c tThe effect of UV/Cl 2 disinfection on the biofilm and corrosion of cast iron pipes in drinking water distribution system were studied using annular reactors (ARs). Passivation occurred more rapidly in the AR with UV/Cl 2 than in the one with Cl 2 alone, decreasing iron release for higher corrosivity of water. Based on functional gene, pyrosequencing assays and principal component analysis, UV disinfection not only reduced the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(68 citation statements)
references
References 41 publications
(42 reference statements)
1
67
0
Order By: Relevance
“…Previous studies have verified that the redox cycling of iron induced by IRB and NRB enhanced the precipitation of iron oxides and formation of Fe 3 O 4 [27,28]. IOB Sediminibacterium could convert ferrous iron to ferric forms, which could be deposited on their cell walls to create voluminous sheaths of iron metabolites [29].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies have verified that the redox cycling of iron induced by IRB and NRB enhanced the precipitation of iron oxides and formation of Fe 3 O 4 [27,28]. IOB Sediminibacterium could convert ferrous iron to ferric forms, which could be deposited on their cell walls to create voluminous sheaths of iron metabolites [29].…”
Section: Discussionmentioning
confidence: 93%
“…Bacillus species belonging to NRB also could affect iron corrosion and modify the corrosion products [29]. Some studies found that the oxidation and reduction of iron occurred simultaneously by the respiration of Azospira and Dechloromonas at nitrate-N concentrations less than 7 mg/L, resulting in Fe 3 O 4 formation [10,27,31]. In SW and GW, the nitrate-N concentrations were 5.1-7.9 and 0.87-2.2 mg/L, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Xu et al [23] found that a nitrate reducer was more corrosive than typical SRB by pitting data under strict anaerobic conditions. On the other hand, the nitrate-dependent Fe(II) oxidation from nitrate-reducing bacteria (NRB) metabolism has the potential to contribute to a dynamic iron redox cycle in freshwater sediments [16], which has been proven inhibiting iron corrosion [24]. Additionally, more and more studies have begun to show protective effects against corrosion by some bacterial biofilms on metal.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of pipe materials to support drinking water biofilm varies dramatically from plastic to metal pipes as they exhibit different degrees of surface roughness and chemical activity [21]. Three main groups of materials have been specified.…”
Section: Physical Characteristics Of the Systemmentioning
confidence: 99%
“…Most of biofilm research in DWDSs is based on studying the influence of the hydraulic conditions, the physical characteristics of the distribution system and the physico-chemical characteristics of the circulating water, among others, on biofilm development, besides from the interactions among microorganisms [19]. Although numerous studies have been carried out in relation to the influence that a number of characteristics of the DWDSs have on biofilm development [10,[20][21][22], in most cases, these characteristics are studied individually or in pairs, at most. Distribution systems are the major components of water utilities.…”
Section: Introductionmentioning
confidence: 99%